Chasing Dragons in the Dragon’s Land: A Convoluted Struggle with Drugs and Deviance in Modern China - Haider, Aftab; Ali, Ashraf; Zubair, Muhammad (Asketik: Jurnal Agama dan Perubahan Sosial, 2023)
This paper discusses the war against drugs in China – from historical Opium Wars to contemporary issues with synthetic narcotics. This paper will thoroughly delve into the intricate interactions of governmental policies, public health initiatives, and societal changes. The drug scenario in China, previously opium-centric is now a cocktail of different drugs such as designer and misuse of prescription drugs.. We will analyze reasons for this change, which include social and economic pressures as well as impact of the digital world. This paper will focus on different ways through which China has been addressing the drug problem ranging from harsh crackdowns to more lenient harm reduction approaches that emphasize treatment and rehabilitation. We will assess how well these policies have worked, emphasizing successes, areas that need enhancement and any inadvertent consequences. But dealing with drug issues is not only about the rules; it’s also about smart healthcare decisions. Healthcare interventions, educational programs, and community outreach efforts designed to address the issue at its roots. These challenges include eliminating the stigma of using drugs, improving access to drug treatment, and mainstreaming harm reduction in discussions. It supports the development of policies that are flexible and based on evidence, focused more on public health as well as with law enforcements. This is the only approach that will allow us to deal with the problem properly, not just running after the dragon and making sure its shadow does not cast itself over a bright image of this nation.